ELECTRONIC PORTABLE ARTICULATION MIRROR (EPAM): MEDIA UNTUK MENINGKATKAN BAHASA MIMIK ANAK TUNARUNGU - Burnyanuddin, Erbi; Bowo, Doni; Junianto, Rizki (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
Abstract Communication is a fundamental human need to interact with each other. For children with special needs, particularly children with hearing impairment, communication becomes very important because they must learn to communicate harder than the normal ones. In Karnna Manohara Special School an articulation mirror is used as a device to train children with hearing impairment in communication, especially in terms of facial expressions. Unfortunately, however, the device is less effective because it is large and not portable. The purpose of this program is to implement Electronic Portable Articulation Mirror (EPAM) which is a modification of a large mirror articulation into a portable, practical and more effective one. This program is conducted through several steps, namely observation, device improvement, feasibility test (calibration), evaluation and revision, application of device, and evaluation. The results of this program is EPAM design that consists of a mirror, an LCD display, a control menu, sound indicator light, power indicator light, power button, display baterray checker, 3.5 mm audio port, audio port 7 mm, charger port, speakers, headsets, and microphone. The implementation of EPAM in speech therapy business unit of Karnna Manohara Special School has succeeded in increasing the facial expressions of the deaf children with the gain of 0.72 and increasing the capacity with a high criterion.